Indium metal-organic framework with catalytic sites coated conductive graphene for high-performance lithium-sulfur batteries. Issue 12 (15th June 2022) - Jiao, Xuechao; Deng, Teng; Men, Xinliang; Zuo, Yinze; Wang, Juan
Abstract: Metal-organic frameworks (MOFs) with abundant active sites and stable frame structures have great advantages for inhibiting the "shuttle effect" and alleviating volume expansion in lithium-sulfur (Li–S) batteries. However, their inherent poor conductivity hinders their application in Li–S batteries. Herein, with isophthalic acid (IPA) as the organic ligand and indium ions as the central metal, a tetrahedral cubic indium MOF (In-IPA) was synthesized and employed for the first time as a sulfur host. Experimental results suggest that In-IPA has a good catalytic effect on the conversion of polysulfides. Furthermore, three-dimensional In-IPA was coated with reduced graphene oxide (rGO) by the hydrothermal method (In-IPA@rGO). The interlaced rGO network not only significantly enhances the conductivity of In-IPA but also improves the reduction of kinetic reactions and promotes electron transport. Finally, In-IPA@rGO exhibited excellent electrochemical performance as a sulfur host. In particular, it exhibited a considerable initial capacity of 1672.3 mAh g −1 at 0.2 C and a reversible capacity of 898.7 mAh g −1 after 100 cycles. In addition, the initial capacity reached 1376.7 mAh g −1 and retained 519.8 mAh g −1 after 200 cycles at 0.5 C. This work proves that nontransition metal-organic frameworks prepared along with highly conductive rGO have synergistic advantages in Li–S battery applications.